Epistemological Components for Degree Work, at the School of Economics and Business (UTE) - Andino-Sosa, Patricio (2015)
This paper aims to present an improvement in the implementation of the work Degree, held at the Business and Economics Sciences School of the Equinoctial Technological University, Quito - Ecuador. It presents a historical evolution of the overall certification process, and it analyzes the several problems that have arisen in the planning and development of the work degree. It has incorporated innovations that were implemented, the comments and analysis that were generated by teachers, students and academic directors. The discussion provides elements of reflection about the impact of methodological research formats, quality of work qualification, for the process of student training, institutional accreditation process and generation of knowledge.